Assessing Road Network Connectivity, Robustness, and Accessibility in Chautara Sangachowkgadhi Municipality - Poudel, Nabaraj; Devkota, Bishnu Prasad (Journal on Transportation System and Engineering, 2025)
Road networks are crucial not only for connectivity and accessibility but also for disaster response and recovery. This study evaluates the connectivity, robustness, and accessibility of the road network in Chautara Sangachowkgadhi Municipality, Sindhupalchowk District. Using hand-held GPS devices, travel distances and times were recorded, while travel costs were gathered through local interviews. Demographic data was obtained from municipal reports and local consultations. Analysis of the road network, represented in a 198x198 matrix, revealed low connectivity (γ = 0.442), complexity (β = 1.313), and circuitry (α = 0.161), indicating that the network is insufficiently connected. A custom desktop C-program application was developed to evaluate network metrics and offer potential applications in other municipalities. The Minimum Spanning Tree (MST) analysis showed that 48% of the distance, 44% of travel cost, and 42% of travel time are required for minimal connection, with 82% of the links identified as critical. Node analysis indicated that node 41 ("Aaldanda") has the highest degree of connectivity, while 111 nodes are moderately connected. Wards 2, 6, 11, 12, and 14 were found to have the poorest accessibility. The study concludes that the existing road network is poorly connected, with many links critical for disaster preparedness and low accessibility to service centers. It is recommended to add new road linkages, with priority given to words 2, 6, 11, 12, and 14.